The Cambridge companion to the musical - Everett, William A., 1962-; Laird, Paul R. (New York : Cambridge University Press, 2002)
Contains fourteen essays that combine to provide a history of musical theater in England and America as it has developed over the course of the twentieth century.
Includes bibliographical references and index.
Adult
Keywords: Musical theater -- History; Musicals -- History and criticism; Musicals -- History and criticism; Theater -- History